Highly electrostrictive salt cocrystal and the piezoelectric nanogenerator application of its 3D-printed polymer composite - Sahoo, Supriya; Panday, Rishukumar; Kothavade, Premkumar; Sharma, Vijay Bhan; Sowmiyanarayanan, Anirudh; Praveenkumar, Balu; Zareba, Jan K.; Kabra, Dinesh; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (ACS Applied Materials and Interfaces, 2024)
Ionic cocrystals with hydrogen bonding can form exciting materials with enhanced optical and electronic properties. We present a highly moisture-stable ammonium salt cocrystal [CH3C6H4CH(CH3)NH2][CH3C6H4CH(CH3)NH3][PF6] ((p-TEA)(p-TEAH)PF6) crystallizing in the polar monoclinic C2 space group. The asymmetry in (p-TEA)(p-TEAH)PF6 was induced by its chiral substituents, while the polar order and structural stability were achieved by using the octahedral PF6- anion and the consequent formation of salt cocrystal. The ferroelectric properties of (p-TEA)(p-TEAH)PF6 were confirmed through P-E loop measurements. Piezoresponse force microscopy (PFM) enabled the visualization of its domain structure with characteristic ``butterfly'' and hysteresis loops associated with ferro- and piezoelectric properties. Notably, (p-TEA)(p-TEAH)PF6 exhibits a large electrostrictive coefficient (Q(33)) value of 2.02 m(4) C-2, higher than those found for ceramic-based materials and comparable to that of polyvinylidene difluoride. Furthermore, the composite films of (p-TEA)(p-TEAH)PF6 with polycaprolactone (PCL) polymer and its gyroid-shaped 3D-printed composite scaled-up device, 3DP-Gy, were prepared and evaluated for piezoelectric energy-harvesting functionality. A high output voltage of 22.8 V and a power density of 118.5 mu W cm(-3) have been recorded for the 3DP-Gy device. Remarkably, no loss in voltage outputs was observed for the (p-TEA)(p-TEAH)PF6 devices even after exposure to 99% relative humidity, showcasing their utility under extremely humid conditions.
Keywords: 3D printing; cocrystals; energy harvesting; ferroelectricity; Piezoelectricity

Silylene-copper(i) catalysis: regioselective protoboration of terminal alkynes - Kaulage, Sandeep H.; Shah, Brij Kumar; Panday, Rishukumar; Sharma, Himanshu; Vanka, Kumar; Khan, Shabana (Chemical Communications, 2025)
Herein, we report an efficient regioselective protoboration of the terminal alkynes catalyzed by newly synthesized silylene-copper(i)-aryl complexes. This method offers a broad substrate scope, good functional-group compatibility, and a gram-scale synthetic ability. The insight into the mechanistic cycle is also provided with the support of experimental and theoretical studies.

Harnessing strong chiroptical nonlinearity in carbene-copper-amides through center-specific chirality: an approach to amplified dissymmetry - Ghosh, Moushakhi; Tanwar, Riteeka; Panwaria, Prakash; Chatterjee, Abhijit; Panday, Rishukumar; Akhtar, Ruksana; Venugopal, Geethu; Mandal, Pankaj; Khan, Shabana (Journal of the American Chemical Society, 2026)
We present the design, synthesis, and photophysical characterization of a new class of chiral N-heterocyclic carbene (NHC)-copper(I)-amide (CMA) complexes with enantiomerically pure phenylethylamine motifs within the amide framework. These chiral CMA complexes represent a new class of mononuclear molecular Cu(I) complexes exhibiting pronounced chiral nonlinear optical (NLO) activity, which are actively being researched for advanced optoelectronic applications such as advanced photonics, biosensing, and security. The intrinsic molecular chirality and noncentrosymmetric crystal packing collectively enable strong second-harmonic generation (SHG) responses in the presence of circularly polarized (CP) light. Notably, these complexes display impressive SHG circular dichroism factors (g SHG-CD) as high as +/- 0.40 at 1000 nm, equaling or surpassing state-of-the-art chiral perovskites in this domain. Beyond their exceptional NLO response, the complexes exhibit dual emissive behavior, originating from both singlet and triplet excited states, with absolute quantum yields reaching 30%, and validated by TD-DFT calculations. The air-sensitive phosphorescence (similar to 550 nm) efficiently generates singlet oxygen (1O2), confirmed by PPh3 photooxidation and TEMPO radical generation. Remarkably, the emission can be reversibly switched between pure singlet and mixed singlet-triplet states by external modulation of O2, maintaining photostability over multiple oxic-anoxic cycles up to 5 days. These findings establish chiral CMA complexes as a new class of NHC-ligated molecular Cu(I) systems to display circularly polarized NLO activity with reversible photoluminescent switching, opening new avenues for exploring main-group organometallic compounds in next-generation polarization-sensitive photonic devices.

Proton conductivity in a copper(II) bipyridine glycoluril complex: the synergistic role of coordinated water and hydrogen-bonded networks - Khatavkar, Medhavi D.; Panday, Rishukumar; Singh, Mayank U.; Kurungot, Sreekumar; Kumbhar, Avinash S. (Inorganica Chimica Acta, 2026)
A dinuclear complex of copper(II) and bipyridine glycoluril (BPG) ligand is synthesized, characterized, and structurally examined by single-crystal X-ray diffraction. The complex [Cu2(BPG)2(NO3)2(H2O)4](NO3)2 center dot 5H2O (complex (1)) further forms a supramolecular network sustained by H-bonds between NH/C=O of BPG, coordinated/free water molecules, and nitrate anions. The complex exhibits a proton conductivity of 5.99 x 10_ 3 S center dot cm_ 1 at 90 degrees C and 95 % relative humidity (RH) with activation energy value Ea 0.35 eV, suggesting the Grotthuss proton transport mechanism. This value is consistent with those reported for proton-conducting systems in which coordinated water molecules play a critical role in facilitating efficient proton hopping across hydrogen-bonded networks.
Keywords: Coordinated water; Copper(II) complex; H -bonding; proton conduction; Supramolecular networks